2005
DOI: 10.1073/pnas.0509269102
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the mid-region of tropomyosin: Bending and binding sites for actin

Abstract: Tropomyosin is a two-chain ␣-helical coiled coil whose periodic interactions with the F-actin helix are critical for thin filament stabilization and the regulation of muscle contraction. Here we deduce the mechanical and chemical basis of these interactions from the 2.3-Å-resolution crystal structure of the middle three of tropomyosin's seven periods. Geometrically specific bends of the coiled coil, produced by clusters of core alanines, and variable bends about gaps in the core, produced by isolated alanines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
146
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(158 citation statements)
references
References 59 publications
11
146
0
1
Order By: Relevance
“…5 B and C. The multiple weak but specific electrostatic interactions between Tm, actin, and myosin allow dynamic regulation of the thin filament that must change its functional state rapidly and in a cooperative manner. The mutations in the first and second halves of periods also approximately correspond to the α-and β-bands of Tm that (33,34) in a 8 Å rigor actin-Tm-myosin S1 complex determined by cryo-EM (10). A minor modification was made in the axial and rotational alignment of Tm in the EM model by positioning crystal structures of Tm fragments to optimize electrostatic interactions of the mutated Tm residues in second-half of P3-P6 with charged residues on actin and myosin, while maintaining the azimuthal alignment.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…5 B and C. The multiple weak but specific electrostatic interactions between Tm, actin, and myosin allow dynamic regulation of the thin filament that must change its functional state rapidly and in a cooperative manner. The mutations in the first and second halves of periods also approximately correspond to the α-and β-bands of Tm that (33,34) in a 8 Å rigor actin-Tm-myosin S1 complex determined by cryo-EM (10). A minor modification was made in the axial and rotational alignment of Tm in the EM model by positioning crystal structures of Tm fragments to optimize electrostatic interactions of the mutated Tm residues in second-half of P3-P6 with charged residues on actin and myosin, while maintaining the azimuthal alignment.…”
Section: Discussionmentioning
confidence: 86%
“…1) are close to actin residues D25, K326, K328, and P333 (23,33,40). The weak but specific electrostatic interactions with actin place Tm in the closed position in the absence of myosin, partially occupying the myosin binding site on actin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical data also has suggested that TnT modulates the equilibrium between closed and open states (28). The proposed azimuthal shift of tropomyosin between blocks IV and V is supported by tropomyosin crystal structures (29), which showed that the coiled coil is disturbed around residues 151-162, located in the C-terminal half of block IV. The flexibility generated by an alanine cluster (Ala-151, 155, and 158) and nearby Tyr-162 in the coiled-coil core would also help accommodate the difference in the azimuthal position between blocks IV and V. When the alanine cluster (156-162) is replaced, the actin-activated myosin ATPase is suppressed (30).…”
Section: Implications For Regulation Of Striated Muscle Contractionmentioning
confidence: 87%
“…Some tropomyosin heptad repeats deviate from the canonical pattern in having either bulky or small hydrophobic residues in positions a and d (10). It has been proposed (11) that the small side chains might be able to move within the large holes facilitating the flexibility required for tropomyosin's wide range of functions on actin filaments and this has been verified experimentally (12). Tropomyosin (284 residues in most isoforms) also has a 7-fold (Ϸ40 residue) sequence repeat (13), and each motif is thought to interact similarly with one actin monomer (8,11).…”
mentioning
confidence: 96%